2011
DOI: 10.1007/s10956-011-9319-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Science Education Game on Students’ Learning and Perception of Inhalants as Body Pollutants

Abstract: This study investigated the knowledge gains and attitude shifts attributable to a unique online science education game, Uncommon Scents. The game was developed to teach middle school students about the biological consequences of exposure to toxic chemicals in an environmental science context, as well as the risks associated with abusing these chemicals as inhalants. Middle school students (n = 444) grades six through eight participated in the study consisting of a pre-test, three game-play sessions, and a dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 29 publications
2
44
2
3
Order By: Relevance
“…The high acceptability ratings for the game are encouraging for further research on the ability of ''Fitter Critters'' to improve healthy eating and activity. Studies of health videogames used in school to increase health knowledge reported satisfaction and usability ratings ranging from 3.39 to 3.75 on a 5-point scale, 10,11 which is lower than the mean ratings observed in the present study. As satisfaction and usability appear to be correlated with knowledge gained, the high acceptability of ''Fitter Critters'' has implications for its ability to impact health knowledge and ultimately behavior.…”
contrasting
confidence: 97%
See 3 more Smart Citations
“…The high acceptability ratings for the game are encouraging for further research on the ability of ''Fitter Critters'' to improve healthy eating and activity. Studies of health videogames used in school to increase health knowledge reported satisfaction and usability ratings ranging from 3.39 to 3.75 on a 5-point scale, 10,11 which is lower than the mean ratings observed in the present study. As satisfaction and usability appear to be correlated with knowledge gained, the high acceptability of ''Fitter Critters'' has implications for its ability to impact health knowledge and ultimately behavior.…”
contrasting
confidence: 97%
“…The health meter changes based on the Critter's diet and physical activity. The diet meters represent daily nutritional requirements, based on the USDA recommendations for children [8][9][10][11][12] years old, and fill as the player feeds the Critter. Meters reset daily so they can be filled again the next time the player logs on.…”
Section: Meters the Game Displays Meters Representing Thementioning
confidence: 99%
See 2 more Smart Citations
“…7 Games have been used in several prevention and cessation programs in high school students and adults, [8][9][10][11] and previous research has shown the use of electronic games as an effective method for increasing content knowledge about the risks of drugs and alcohol use for adolescents. [12][13][14][15] Additionally, researchers found that a computer-based, interactive substance abuse treatment and prevention program increased drug abuse prevention knowledge and decreased the frequency of smoking among adolescents. 16 For example, in a meta-analysis of computerdelivered interventions for alcohol and tobacco use, researchers analyzed the effect sizes from 42 randomized controlled trials, and found the average weighted effect size (d) across the studies to be 0.20, p < 0.001.…”
Section: Introductionmentioning
confidence: 99%